Inequalities in ownership and availability of home-based vaccination records in 82 low- and middle-income countries - Aluísio J D Barros; Cesar G Victora; Daniel R Hogan; M Carolina Danovaro-Holliday; Bianca O Cata-Preta; Thiago M Santos; Andrea Wendt; Luisa Arroyave; Tewodaj Mengistu (BMJ Global Health)
Introduction Home-based records (HBRs) are widely used for recording health information including child immunisations. We studied levels and inequalities in HBR ownership in low-income and middle-income countries (LMICs) using data from national surveys conducted since 2010.Methods We used data from national household surveys (Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS)) from 82 LMICs. 465 060 children aged 6–35 months were classified into four categories: HBR seen by the interviewer; mother/caregiver never had an HBR; mother/caregiver had an HBR that was lost; and reportedly have an HBR that was not seen by the interviewer. Inequalities according to age, sex, household wealth, maternal education, antenatal care and giving birth in an institutional setting were studied, as were associations between HBR ownership and vaccine coverage. Pooled analyses were carried out using country weights based on child populations.Results An HBR was seen for 67.8% (95% CI 67.4% to 68.2%) of the children, 9.2% (95% CI 9.0% to 9.4%) no longer had an HBR, 12.8% (95% CI 12.5% to 13.0%) reportedly had an HBR that was not seen and 10.2% (95% CI 9.9% to 10.5%) had never received one. The lowest percentages of HBRs seen were in Kiribati (22.1%), the Democratic Republic of Congo (24.5%), Central African Republic (24.7%), Chad (27.9%) and Mauritania (35.5%). The proportions of HBRs seen declined with age and were inversely associated with household wealth and maternal schooling. Antenatal care and giving birth in an institutional setting were positively associated with ownership. There were no differences between boys and girls. When an HBR was seen, higher immunisation coverage and lower vaccine dropout rates were observed, but the direction of this association remains unclear.Interpretation HBR coverage levels were remarkably low in many LMICs, particularly among children from the poorest families and those whose mothers had low schooling. Contact with antenatal and delivery care was associated with higher HBR coverage. Interventions are urgently needed to ensure that all children are issued HBRs, and to promote proper storage of such cards by families.